Influence of impulse magnetic fields of extremely low frequencies on H2O2- and Fe2+-induced free radical lipid oxidation in liposomal suspensions - Martynyuk, V. S.; Tseyslyer, Yu. V. (Biophysical Bulletin, 2022)
Background: For a long time, special attention in experimental biology and medicine is paid to free radical processes involving reactive oxygen species. In electromagnetic biology, the interest in free radical oxidation in biological membranes has increased significantly due to the discovery of spin mechanisms of magnetic fields on free radical processes. In the present day, these mechanisms are considered to be key in the processes of magnetoreception in living organisms. Liposomes, as the simplest models of biological membranes, are often used to study the primary mechanisms of action of different factors on the structural and functional properties of membranes. However, the influence of ecological significant extremely low-frequency magnetic fields on free radical oxidation in liposomal suspensions has not been studied enough. Objectives: The elucidation of the peculiarities of the influence of the extremely low frequency pulsed magnetic fields (ELF PMF) on H2O2- and Fe2+-induced peroxidation of natural phospholipids in liposomal suspensions. Materials and methods: The liposomal suspensions in phosphate buffer pH=7.4 were used. According to the literature and own results on light scattering the average diameter of liposomes was about 500Å. Ultra-weak chemiluminescence of liposomal suspensions was recorded using a device that operated in the mode of single photons counting. It consisted of a light-insulated cuvette unit where the test samples were placed, as well as a temperature sensor and a solenoid, which was used to create the PMF. Optical contact of the test samples with the photoelectron multiplier was carried out using a light guide. The recording system consisted of a broadband photomultiplier tube detector — FEU-130, which was at a temperature of –20°C. The pulse analyzer AI-256 was used to separate the useful signal that corresponded to the registration of single chemiluminescence light quanta. The voltage on the photomultiplier tube detector was applied in the range of current-voltage characteristics of this detector, in which a random voltage fluctuation had a minimal effect on the measurement of the useful signal. The number of light quanta that were recorded for defined time intervals characterized the overall intensity of the process of free radical oxidation of lipids in the experimental samples. The pulsed magnetic field was created using a solenoid coil located in the cuvette part. PMF was created using a serial generator G6-28. The magnetic field pulses were rectangular in shape with variable polarity for a period of oscillations. The induction of PMF was monitored using microteslameter G-79. The series of extremely low frequencies (5–80 Hz) and induction (5–500 μT) of PMF was chosen due to their environmental and physiological significance. Results: PMF of different frequencies with induction of 5 and 50 μT did not affect (p>0.05) H2O2- and Fe2+-induced lipid oxidation in liposomal suspensions. Statistically significant changes (p<0.05) were revealed only when liposomal suspensions were exposed to PMF with induction of 500 μT. It was found that the action of PMF with the frequency of 8 Hz 500 μT significantly inhibited H2O2-induced and enhanced Fe2+-induced chemiluminescence. This effect is associated with inhibition of the decomposition and with the accumulation of phospholipid hydroperoxides, which decompose and recombine in the presence of Fe2+ ions, which is accompanied by stronger chemiluminescence. The study of the dependence of the dynamics of the chemiluminescence intensity on the frequency of the PMF indicates the presence of a certain dependence of the effects in the range of up to 30 Hz. However, the inhibitory effect of PMF for the H2O2-induced oxidation phase is not always accompanied by a statistically significant increase in the amplitude of Fe2+-dependent light flash of chemiluminescence that indicates the general inhibitory effect of PMF at a certain frequency. Conclusions: PMF of extremely low frequencies statistically significantly affects the free radical oxidation in liposomal suspensions only at inductions exceeding several hundred microteslas. This indicates the effect of PMF on free radical processes for the conditions of the selected membrane model is realized mainly through spin interactions that determine the recombination of free radicals. The decrease of induction by one or two orders of magnitude, as well as increasing in frequency of the PMF above 50 Hz, leads to a decrease in the effectiveness of the influence of this physical factor on the intensity of lipid-free radical oxidation in liposomal suspensions. The most sensitive to the influence of ELF PMF is the phase of H2O2-induced free radical oxidation of lipids.